Altered expression of OsNPF7.1 and OsNPF7.4 differentially regulates tillering and grain yield in rice. (June 2019) - Huang, Weiting; Nie, Haipeng; Feng, Fei; Wang, Jie; Lu, Kai; Fang, Zhongming
Highlights: The expression patterns of OsNPF7.1 and OsNPF7.4 were opposite in axillary buds under different nitrogen concentrations. Overexpression and knockout experiments revealed that OsNPF7.1 and OsNPF7.4 are involved in determining the axillary bud outgrowth, and thereby, influence the tiller number and grain yield in rice. Our study provides an alternative way to modify the rice architecture and enhance the grain yield by regulating the expression of OsNPF7.1 and OsNPF7.4 . Different members in the NPF family have different roles in rice. Abstract: The rice nitrate and di/tripeptide transporter (NPF) gene family plays an indispensable role in nitrogen transport and plant growth. In this study, 18 alternatively spliced OsNPF genes with 36 different forms of mRNAs were identified, and two of these, namely OsNPF7.1 and OsNPF7.4, showed opposite expression patterns in axillary buds under different nitrogen concentrations. Our results indicate that the expression levels of OsNPF7.1 and OsNPF7.4 determine the axillary bud outgrowth, especially for the second bud, and subsequently influence the tiller number in rice. The overexpression of either of the variants of OsNPF7.1 or the knockout of OsNPF7.4 increased the seedling biomass as well as the tiller number, filled grain number, and grain yield in rice. However, the RNAi-mediated silencing of OsNPF7.1 or the overexpression of either of the variants of OsNPF7.4 had an opposite effect. The overexpression of OsNPF7.1 or OsNPF7.4 could improve the uptake of nitrate, but the OsNPF7.4- overexpressing plants had lower biomass. It is possible that excessive nitrate in the OsNPF7.4 -overexpressing plants led to the accumulation of amino acids in the leaf sheath, which inhibited seedling biomass. In addition, the reduced reutilization of nitrate in the seedlings also limited the plant biomass. However, the moderate increase in nitrate and amino acid concentrations in the OsNPF7.1 -overexpressing plants could promote seedling biomass and enhance grain yield. In conclusion, our data suggest that different members in the NPF family have different roles in rice, and this study suggests an alternative way to modify rice architecture and enhance grain yield by regulating the expression of OsNPF7.1 and OsNPF7.4 .